Numerical simulation of mixed convection in a square cavity using Direct Meshless Local Petrov-Galerkin (DMLPG) method. (February 2019) - Pranowo,; Tri Wijayanta, Agung
Abstract: This paper present the extension of the Direct Meshless Petrov-Galerkin (DMLPG) for solving mixed convection heat transfer in a square cavity for the flow up to Reynolds number up to Re 400 and Grashof number Gr = 100. The semi algebraic forms of the governing equations are solved using fractional step method. The numerical results of the DMLPG method are in good agreement with the conventional numerical results in the literature. Based on the numerical results it is shown that The DMLPG is very promising in dealing with the fluid flow and heat transfer problem.